2012
DOI: 10.1061/(asce)ee.1943-7870.0000475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methane Oxidation Efficiency of Two Biocovers: Field and Laboratory Results

Abstract: Biocovers constitute a promising technology to reduce fugitive and residual emissions from landfills throughout their operational life and after gas collection systems are turned off. The aim of this study was to assess the efficiency of two substrate materials to oxidize CH4 into CO2 under field conditions and in the laboratory (column tests). The two substrates evaluated were: 1) a mixture of sand and compost, and 2) a mixture of the sand-compost with gravel. The oxidation rates obtained in the field attaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Biological cover that has been recommended by the authors of [10] can solve the above-mentioned problems. It optimizes the environmental conditions of the cover, enhances the CH 4 oxidation rates, and reduces the CH 4 fluxes emitted from landfills [11][12][13]. Biochar is a porous, organic material produced by the pyrolysis or gasification of waste biomass, and the increased presence of micropores makes it highly preferable for gas adsorption purposes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Biological cover that has been recommended by the authors of [10] can solve the above-mentioned problems. It optimizes the environmental conditions of the cover, enhances the CH 4 oxidation rates, and reduces the CH 4 fluxes emitted from landfills [11][12][13]. Biochar is a porous, organic material produced by the pyrolysis or gasification of waste biomass, and the increased presence of micropores makes it highly preferable for gas adsorption purposes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that a passive biosystem (where the biogas passes through the cover naturally, without pumping it) installed in the cover system (interim or fi-nal) can be a very effective complement to active systems in reducing fugitive emissions of methane and odorous substances (Abichou et al, 2006a;Cabral et al, 2010a;Capanema et al, 2013;Capanema et al, 2014;Geck et al, 2016;Lucernoni et al, 2016;Roncato and Cabral, 2012;Sadasivam and Reddy, 2014;Scheutz et al, 2009). Most of these studies documented the performance of passive biosystems in temperate climates, while (to the authors' knowledge) no field-scale studies have been performed to document the performance of passive biosystems in Brazil (a tropical country) and employing residual soils.…”
Section: Introductionmentioning
confidence: 99%
“…To date, extensive research conducted in this field highlights the importance of employing organic rich biocover materials to improve the microbial methane oxidation capacity of landfill cover systems (Park et al, 2004;Stern et al, 2007;Huber-Humer et al, 2008Scheutz et al, 2011;Roncato and Cabral, 2011). However, researchers have not yet explored the process of methane adsorption within landfill cover systems that can also contribute to methane mitigation.…”
Section: Introductionmentioning
confidence: 99%